Domestic Violence against Married Women in Kaski District, Nepal - Baral, Shrijana (Janapriya Journal of Interdisciplinary Studies, 2020)
Violence against women is a very complex and widespread issue in different societies. This study was done to identify the experience and causes of domestic violence in Nepalese context. The main objective of this study was to assess domestic violence among reproductive aged women of 15-49 years in Pokhara Sub Metropolitan city of Kaski, Nepal. A cross-sectional descriptive research design was used for this study. Samples were selected from multistage sampling technique. Semi-structured interview schedule was used. After analyzing data, it was found that (41%) of the respondents belong to the age group 35-44 years of age. Most of the females (89.5%) faced different kind of violence in their life from their family members. Women are suffering from psychological violence 84.2%, physical violence 83.2%, sexual violence 86.3% and cultural violence 87.4%. The causes of the violence are disobeying the husband 96.8% and alcoholism. Most of women’s husband 82.10% had habit of drinking alcohol. Women are being violated by their husband as well as their family members. There is a high prevalence of violence among female who are involved in labor work. Despite of high level of violence, women are not working against it in order to maintain their confidentiality and fear of losing their social prestige. Domestic violence is the most thoughtful social condition that threatens women’s physical and mental health. It is also legal and health challenges on women’s health and happiness. It is one of the most important issues so awareness is necessary for social justice.